Integritas di Balik Layar: Mengapa Etika adalah Fondasi Utama Manajemen Sumber Daya Alam - Damanik, Dini Aulia Br; Nasution, Dito Aditia Darma (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article aims to conceptually examine the role of professional ethics in Human Resource Management (HRM) practices and its implications for practitioner integrity, organizational justice, and organizational sustainability. This study adopts a qualitative approach using a literature review method by analyzing relevant primary and secondary sources related to HRM ethics. The findings indicate that professional ethics constitute a strategic foundation underlying HRM policies and practices, particularly in decision-making processes concerning employees’ rights, obligations, and dignity. The integrity of HR practitioners plays a crucial role in building employee trust, strengthening organizational commitment, and fostering an ethical and transparent work culture. Furthermore, ethical challenges in the digital era, including data privacy protection and the risk of algorithmic bias, require high levels of ethical literacy among HR professionals. This article concludes that strengthening professional ethics in HRM is essential not only for organizational effectiveness but also for dignified and sustainable human resource governance